Operative Management of Neonatal Lymphatic Malformations: Lesson Learned From 57 Consecutive Cases - Scuglia, Marianna; Conforti, Andrea; Valfrè, Laura; Totonelli, Giorgia; Iacusso, Chiara; Iacobelli, Barbara D.; Meucci, Duino; Viggiano, Milena; Fusaro, Fabio; Diociaiuti, Andrea; Morini, Francesco; El Hachem, May; et al. (Frontiers in Pediatrics, 2021)
Aim of the study: Lymphatic malformations (LMs) are rare entities, sometimes difficult to treat, that may be life-threatening when intricately connected to airway structures. Invasive treatments are occasionally required, with sclerotherapy considered the treatment of choice and surgery as a second-line approach. The aim of the present study was to evaluate our multidisciplinary team experience in treating newborns affected by LMs requiring operative management, while defining early outcomes. Methods: Retrospective review of all consecutive patients admitted for LMs requiring operative management between January 2000 and January 2019. Patients were mainly characterized based on anatomical district of the LM (and further stratified based on the development of respiratory distress), need for tracheostomy, number of sclerotherapies, indication for surgery, and residual disease beyond the 1st year. Morbidity and mortality were also evaluated. Fisher exact test and Mann–Whitney test were used as appropriate. Statistical significance was set at p < 0.05. Results: Fifty-seven patients were included in the study, 36 with cervicofacial and/or mediastinal LMs and 21 with LMs of other anatomical districts. Due to the risk of developing respiratory distress at birth, patients with cervicofacial and/or mediastinal LMs were divided into two groups (8/36 group A vs. 28/36 group B). Group A patients are at higher risk for tracheostomy (7/8 group A vs. 1/28 group B, p = 0.0001) and more often require surgical reduction of the residual lymphatic abnormality (5/8 group A vs. 4/28 group B, p = 0.013). They also require sclerotherapies more often, but the difference is not statistically significant (8/8 group A vs. 19/28 group B, p = 0.15). Patients with cervicofacial/mediastinal LMs frequently suffer from persistent residual disease beyond the 1st year of life, significantly more often in group A (7/8 group A vs. 12/28 group B, p = 0.043). Conclusion: LMs are rare conditions with potential life-threatening behavior. Their intrinsic clinical complexity requires a multidisciplinary approach to the affected patients. Planning a long-term follow-up is essential because of the late-term problems those patients may experience.